The Coulomb Hole of the Ne Atom - Rodríguez‐Mayorga, Mauricio (ChemistryOpen, 2019)
We analyze the Coulomb hole of Ne from highly‐accurate CISD wave functions obtained from optimized even‐tempered basis sets. Using a two‐fold extrapolation procedure we obtain highly accurate results that recover 97 % of the correlation energy. We confirm the existence of a shoulder in the short‐range region of the Coulomb hole of the Ne atom, which is due to an internal reorganization of the K‐shell caused by electron correlation of the core electrons. The feature is very sensitive to the quality of the basis set in the core region and it is not exclusive to Ne, being also present in most of second‐row atoms, thus confirming that it is due to K‐shell correlation effects.